Enhancing Maritime Safety Education through Mobile Gamification: Development and Design of an Android-Based Learning Game for Safe Working Practices on Board Ship - Atmaja Septa Miyosa; Aka Shakthi Avri Afika; Restu Bumi Krisaputra Krisaputra; Muhammad Irfan Hanafi; Firdi Kurnia Rahman; Tri Anggraeni; Adi Sucipto (Journal of Information Technology and Its Utilization, 2024)
Semarang Maritime Polytechnic (PIPS) requires an Android-based English learning tool that is integrated with courses related to work safety on ships. This study aims to create an English learning tool that is integrated with courses related to work safety on ships in the form of a quiz and is Android-based. The development of this game uses the Game Development Life Cycle (GDLC) method which is a guideline that includes the game development process (Hendrick in Ramadan and Widyani, 2013). This method consists of six development phases: Initiation, Pre-production, Production, Testing, Beta testing, and Release. This application is called "Safe Working Practices on Board Ship" and is expected to be an alternative or new media for students to practice their English language skills while understanding work safety on ships.